Observations of Earth’s Normal Modes on Broadband Ocean Bottom Seismometers - Laske, Gabi (Frontiers in Earth Science, 2021)
It is generally thought that high noise levels in the oceans inhibit the observation of long-period earthquake signals such as Earth’s normal modes on ocean bottom seismometers (OBSs). Here, we document the observation of Earth’s gravest modes at periods longer than 500 s (or frequencies below 2 mHz). We start with our own 2005–2007 Plume-Lithosphere-Undersea-Mantle Experiment (PLUME) near Hawaii that deployed a large number of broadband OBSs for the first time. We collected high-quality normal mode spectra for the great November 15, 2006 Kuril Islands earthquake on multiple OBSs. The random deployment of instruments from different OBS groups allows a direct comparison between different broadband seismometers. For this event, mode S06 (1.038 mHz) consistently rises above the background noise at all OBSs that had a Nanometrics Trillium T-240 broadband seismometer. We also report observations of other deployments in the Pacific ocean that involved instruments of the U.S. OBS Instrument Pool (OBSIP) where we observe even mode S04 (0.647 mHz). Earth’s normal modes were never the initial target of any OBS deployment, nor was any other ultra-low-frequency signal. However, given the high costs of an OBS campaign, the fact that data are openly available to future investigators not involved in the campaign, and the fact that seismology is evolving to investigate ever-new signals, this paper makes the case that the investment in a high-quality seismic sensor may be a wise one, even for a free-fall OBS.